Correlation of distribution of oil palm (Elaeis guinensis Jacq) through image drone with the potential of CO2 uptake at PT. Unggul Widya Teknologi Lestari Pasangkayu Regency, West Sulawesi. Issue 2 (July 2021) - Randa, G; Asrul, L; Rafiuddin,
Abstract: The potential for CO2 uptake in oil palm which is supported by the presence of solar radiation reception space can support the photosynthesis process to take place properly. This study aims to show the correlation between the results of identifying the distribution of oil palm through aerial photographs, namely drones, and the potential for CO2 uptake. The potential for CO2 uptake in oil palms for five samples of planting years is viewed from the aspect of canopy projection space density, cropping patterns, and spacing which is clarified by the allometric multiplied results of the potential CO2 -eq uptake. In general, the five samples of oil palm planting years apply a triangular cropping pattern with a spacing of 9 m × 9 m. The canopy projection for the 2017 planting year, shows that oil palm plants are still at a distance from one another because the canopy is still short, in the 2011 planting year shows the canopy projection that has touched each other but there is still room for receiving solar radiation that can occur evenly so that between the two planting years Oil palms in the planting years 2005, 2003, and 1997 showed a mutually contrasting canopy projection between the oil palms so that even though the space for receiving solar radiation is small. The potential for CO2 uptake was greater because apart from being obtained from the atmosphere, it can also be obtained from understorey plants and organs decomposed plants. It concluded that the higher the density of the distribution of palm oil makes large the potential uptake of CO2 emissions. It is hoped that the identification of the potential for CO2 absorption in oil palm can use a multi-spectral drone as an aerial photo facility.